(untitled) - Kahn, Gilbert (New York, 1969)
Contents: Indexing rules; filing procedures and materials; alphabetic correspondence filing; charge and transfre methods; selecting equipment and supplies; numeric correspondence filing; geographic correspondence filing; subject correspondence filing; card filing - vertical and visible; establishing and maintaining filing systems
Keywords: Filing systems,Hệ thống hồ sơ